Up-regulation of ABCG1 is associated with methotrexate resistance in acute lymphoblastic leukemia cells - Chen, Yao; Fang, Houshun; Sun, Huiying; Wu, Xiaoyu; Xu, Yan; Zhou, Bin-Bing S.; Li, Hui (Frontiers in Pharmacology, 2024)
Acute lymphoblastic leukemia (ALL) is a prevalent hematologic malignancy in children, and methotrexate (MTX) is a widely employed curative treatment. Despite its common use, clinical resistance to MTX is frequently encountered. In this study, an MTX-resistant cell line (Reh-MTXR) was established through a stepwise selection process from the ALL cell line Reh. Comparative analysis revealed that Reh-MTXR cells exhibited resistance to MTX in contrast to the parental Reh cells. RNA-seq analysis identified an upregulation of ATP-binding cassette transporter G1 (ABCG1) in Reh-MTXR cells. Knockdown of ABCG1 in Reh-MTXR cells reversed the MTX-resistant phenotype, while overexpression of ABCG1 in Reh cells conferred resistance to MTX. Mechanistically, the heightened expression of ABCG1 accelerated MTX efflux, leading to a reduced accumulation of MTX polyglutamated metabolites. Notably, the ABCG1 inhibitor benzamil effectively sensitized Reh-MTXR cells to MTX treatment. Moreover, the observed upregulation of ABCG1 in Reh-MTXR cells was not induced by alterations in DNA methylation or histone acetylation. This study provides insight into the mechanistic basis of MTX resistance in ALL and also suggests a potential therapeutic approach for MTX-resistant ALL in the future.